1977
DOI: 10.1139/v77-566
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic applications of the photochemically induced addition of oxycarbinyl species to α-enones. Part II. The addition of ketals, aldehydes, and polyfunctional species

Abstract: Alcohols possessing an α-hydrogen, acetals, and aldehydes undergo photochemically induced conjugate addition to a variety of α-enones to give 1,4-ketols, 1,4-keto ketols and 1,4-diketones respectively. It appears that the aldehydes frequently succeed where acetals and alcohols fail, and acetals where alcohols fail. It is therefore possible to employ polyfunctional addenda and achieve addition at only one of the activated sites. The reactions are always regiospecific and are frequently completely stereoselectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…The key point however in terms of the remarkable reactivity reported here for 2, which as indicated above is assumed to exhibit a conformational preference, is the fact that abstraction of the C 2 hydrogen will be significantly accelerated by both oxygen atoms (h = 7.1, 9.5u). Although this inverts the relative reactivity of 1 and 2 suggested by the EPR spectral data, 7 it is clearly entirely consistent with their behaviour in terms of the photomediated reaction with alkynes reported here. The C 2 hydrogens in the other 2-alkyl-1,3-dioxolanes considered in this study also enjoy favourable stereoelectronic relationships with both oxygen atoms.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The key point however in terms of the remarkable reactivity reported here for 2, which as indicated above is assumed to exhibit a conformational preference, is the fact that abstraction of the C 2 hydrogen will be significantly accelerated by both oxygen atoms (h = 7.1, 9.5u). Although this inverts the relative reactivity of 1 and 2 suggested by the EPR spectral data, 7 it is clearly entirely consistent with their behaviour in terms of the photomediated reaction with alkynes reported here. The C 2 hydrogens in the other 2-alkyl-1,3-dioxolanes considered in this study also enjoy favourable stereoelectronic relationships with both oxygen atoms.…”
supporting
confidence: 89%
“…It has already been shown that 1,3-dioxolanes and 2-substituted-1,3-dioxolanes can participate in this photomediated process, the resulting radicals adding to a,b-unsaturated aldehydes, 5 ketones 6,7 and esters 8 in a synthetically useful way. The corresponding thermal process, based on radical initiators such as AIBN or benzoyl peroxide, is much less efficient with, in some cases, rearrangement of the dioxanyl radical being competitive with its addition to the unsaturated system.…”
mentioning
confidence: 99%
“…299 Typically, an acetonitrile solution of an enone, a large excess of 187, and 16 mol % of benzophenone (photosensitizer) were photolyzed for 5 h at 350 nm. After vacuum distillation, the adduct was obtained in 67% yield.…”
Section: Scheme 146mentioning
confidence: 99%
“…We found this process to be a promising method for carbon-carbon bond formation in carbohydrate chemistry, and also found that reaction with substrate 74 proceeded with complete regio-and stereoselectivity [66,67,68] (Scheme 20a-e). This methodology proved its flexibility with photoinduced addition of bifunctional alcohols (Scheme 20f), acetals [69] (Scheme 20g) and aldehydes [70,71] (Scheme 20h). Subsequent work in our laboratory, allowed us to establish that alcohols possessing anhydrogen, acetals, and aldehydes undergo photochemically induced conjugate addition to a variety of conjugated enones to give 1,4-ketols, 1,4-keto acetals and 1,4-diketones, respectively.…”
Section: Photochemically Induced Addition To Hex-2-enopyranosid-4-ulosesmentioning
confidence: 95%